PENGUKURAN EFISIENSI DAN FAKTOR PENENTU TINGKAT EFISIENSI BANK DI INDONESIA - , Muazaroh, SE.,MT., Prof. Dr. Eduardus Tandelilin, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Banking efficiency is one indicator of performance of banks. Banking efficiency is an indicator to measure the overall performance of banks activities. Efficiency is the use of the lowest input to achieve the maximum amount of output. Efficiency is critical because resources or inputs are limited in the organization The objectives of the study are to measure the efficiency of the banks and identify some determinant factors of bank efficiency in Indonesia. Two stages research methods are employed. First, the score of bank efficiency measured using two concepts, profit and cost efficiency concept using Stochastic Frontier Approach (SFA). Second, the scores obtained are linked to a series of determinants of bank efficiency using regression technique. These factors are bank size, bank capital, bank risk management, bank ownership structure and bank market share. Using the data from 113 banks in Indonesia during the 2005-2009 periods, the results showed that banks in Indonesia are still not efficient in terms of cost and in terms of profit. This is indicated by the average of cost and profit efficiency is less than one. It means that banks in Indonesia have potency to improve the efficiency. Based on the bank category, the most efficient bank is the regional development banks (BPD). This is because the BPD has a higher net interest margin and lower non-performing loans. The most inefficient banks are foreign exchange commercial banks. Foreign exchange commercial banks have high operating costs and are not able to optimize the output for a profit. The determinant factors of cost efficiency are the size of banks, credit risk, bank ownership and market share. The determinant factors of bank's profit efficiency are the size of banks, bank capital, bank ownership and market share. The interesting result in this study is that credit risk is determinant factor of cost efficiency, but not determinant factor of the profit efficiency. It means that bad debts will increase cost of bank, but bank with bad debts still can get higher profit. Banks with higher Non Performing Loan still can generate higher profit, if they can develop other sources of income from securities and fixed income. The economies of scale is existence in Indonesian banking , as indicated by the increase in efficiency when bank assets grow, but once it reaches a certain point the increase of assets will decrease the efficiency. The results of this study have contribution to bank managers, practitioners and policy makers on the relevance of the determinants factors of bank efficiency that can be used by them to improve the banks efficiency and the efficiency of the banking system.